Additive manufacturing of polymer nanocomposites: Needs and challenges in materials, processes, and applications - Ans Al Rashid (14777050) (2021)
Polymer nanocomposites have attracted increasing interest in research and development with several current and potential industrial applications due to their wide margin of superiority over conventional materials. Polymer composites provide a higher strength-to-weight ratio, easily customizable product properties, flexible manufacturing processes, high resistance to corrosion or erosion, and lower cost. The recent progress in additive manufacturing (AM) methods has paved the way for even a broader range of flexibilities in design and materials in several industrial sectors, including aerospace, biomedical, construction, electronics, telecommunication, mechanical, and defense. However, some hindrances remain in the synthesis of polymer composites and their fabrication through AM technologies. A comparative review of AM processes for polymer composites and their applications is presented in this study. This study aims to provide engineers and scientists with an updated understanding of the underlying issues, barriers, limitations, and opportunities. It will also help the reader to systematically reveal the research problems and future directions related to materials synthesis and AM processes. Other Information Published in: Journal of Materials Research and Technology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jmrt.2021.07.016